(untitled) - The World Bank in Vietnam (WB) (Hà Nội, 2003)
The Second Rural Transport Project aims to a) improve the access of rural communities in the project provinces to markets, off-farm economic opportunities, and social services; b) develop central, provincial, and local capacity to improve and sustain the level of service of the rural transport network; and c) foster the development of small-scale private contractors. The project contains five components: 1) this component will provide institutional development support to Project Management Unit (PMU) No.18 and Provincial Departments of Transport to implement the project. This includes a training program to Provincial PMUs in project management and monitoring, technical aspects of road rehabilitation and maintenance, contract management, environmental screening of rural roads, and resettlement and land acquisition. 2) This component will strengthen Ministry of Transport's (MOT) capacity to provide strategic leadership in the rural transport sub-sector. It will help MOT to further develop the rural transport strategy, formulate and implement rural transport policy, and provide the strategic direction of the sub-sector. 3) The component will include the rehabilitation of district, commune, and some provincial roads in the project provinces. 4) This component will support the Rural Transport Unit in developing guidelines for maintenance planning and implementation. 5) This component will provide training to the local construction industry.
Keywords: Highway,Đường bộ,Đường cao tốc,Road; Transportation,Vận tải,Giao thông,Transportation